Why engagement matters in policy implementation: an examination of the engagement of policy actors in the implementation of a mental health and addictions strategy - Heather L. Bullock; John N. Lavis; Gillian Mulvale; Michael G. Wilson; Celine Mulhern (Implementation Science Communications)
Abstract Background Shifts toward “new public governance” (NPG), where policy decisions and their implementation are “co-produced” by a policy network, have captured the attention of policymakers as an approach that may produce better outcomes. It is particularly promising in mental health, where it is increasingly acknowledged that effective change requires actions by multiple actors across a range of policy and system settings. In Ontario, Canada, the government’s recent mental health reform, Open Minds, Healthy Minds, Ontario’s Comprehensive Mental Health and Addictions Strategy, is unique in terms of its scope and the NPG-inspired processes employed. This study addresses two questions: 1) Who was engaged in the implementation of the Strategy and how were they engaged? and 2) How and why did their involvement contribute to the implementation process and early outcomes? Methods We used a single case study design and partnered with the Ontario Ministry of Health. We used two complementary analytical methods: 1) stakeholder analysis, and 2) political landscape analysis. Seventeen interviews were conducted with citizens, government officials and people with lived experience, and 21 documents analyzed using directed content analysis and drawing from theoretical frameworks regarding political and actor-related determinants of implementation. Results Stakeholder analysis highlighted the wide range of interdependent actors involved, the multiple ways they provided input, and the structures utilized. The political landscape analysis revealed the role of interests as having a large influence on the implementation process and early outcomes, particularly political actors’ decision to tie the process to their election platform. Relational and contextual variables, such as the relative instability of the policy actors, had a negative impact on the process, but that was offset by the perceived level of dedication of the individuals involved. Conclusion Our findings point to five practical insights for policymakers and implementers: being attentive to the power distribution among actors, the importance of building and maintaining trust amongst actors, the opportunity-cost of taking a NPG approach, the timing/sequencing of the process, and the need for careful consider of the type of actors involved and the expertise they bring.